Enhancing Nursing Documentation Through Incident Reporting and Safety Training: A Systematic Review - Maulana, Irvan; Setiawan, I Made Benny (Journal of Pubnursing Sciences, 2025)
Background: Accurate nursing documentation is critical for patient safety and quality healthcare; however, many nurses face challenges in incident reporting and effective documentation practices. Objective: This study systematically reviews the relationship between incident reporting, patient safety training, and nursing documentation in hospital settings. Method: A systematic review was conducted following PRISMA guidelines. Relevant studies published from 2020 to 2025 were sourced from databases including PubMed and ScienceDirect. An initial search yielded 392 articles, which were screened for inclusion based on established criteria, resulting in the selection of 10 studies focusing on hospital-based nursing practices. Results: The findings indicate that patient safety training significantly enhances nurses’ understanding and skills in incident reporting, leading to improved quality in nursing documentation. Additionally, a supportive managerial framework and a non-punitive reporting culture are crucial elements that foster a culture of safety within healthcare organizations, encouraging proactive participation among nurses. This review emphasizes the need for structured training programs and strong institutional support to optimize nursing documentation and enhance patient safety. Conclusion: The insights gained from this systematic review provide a foundation for developing effective policies and training initiatives aimed at improving incident reporting and documentation practices within healthcare settings.